2018
DOI: 10.1186/s13229-018-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

The geometric preference subtype in ASD: identifying a consistent, early-emerging phenomenon through eye tracking

Abstract: BackgroundThe wide range of ability and disability in ASD creates a need for tools that parse the phenotypic heterogeneity into meaningful subtypes. Using eye tracking, our past studies revealed that when presented with social and geometric images, a subset of ASD toddlers preferred viewing geometric images, and these toddlers also had greater symptom severity than ASD toddlers with greater social attention. This study tests whether this “GeoPref test” effect would generalize across different social stimuli.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
72
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 72 publications
10
72
1
6
Order By: Relevance
“…In line with many previous studies [Moore et al, 2018;Pierce et al, 2011Pierce et al, , 2015 children in the ASD group generally spent less time looking at the display screen than ones in the TD group and thus the most effective measure for group comparisons is the relative proportion of time spent viewing one stimulus compared with another.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In line with many previous studies [Moore et al, 2018;Pierce et al, 2011Pierce et al, , 2015 children in the ASD group generally spent less time looking at the display screen than ones in the TD group and thus the most effective measure for group comparisons is the relative proportion of time spent viewing one stimulus compared with another.…”
Section: Discussionsupporting
confidence: 79%
“…The proportion of the total fixation time on DSI was used as the dependent variable. In accordance with previous studies [Moore et al, 2018;Pierce et al, 2011Pierce et al, , 2015, the dependent variable was compared to Toy 2 were calculated. In all cases fixation counts and durations were also measured.…”
Section: Discussionmentioning
confidence: 75%
“…It has been proposed that gaze abnormalities in children with ASD may reduce their early exposure to social information and impair their ability of learn basic social skills (Klin, Shultz, & Jones, 2015). Indeed, a common behavioral symptoms of ASD is reduced eye contact (Senju & Johnson, 2009;Tanaka & Sung, 2016) and previous eye tracking studies have reported that children with ASD exhibit weaker gaze preferences for people (Moore et al, 2018;Pierce et al, 2016), faces (Chawarska, Macari, & Shic, 2012;Chita-Tegmark, 2016;Constantino et al, 2017;W Jones, Carr, & Klin, 2008;Warren Jones & Klin, 2013;Papagiannopoulou, Chitty, Hermens, Hickie, & Lagopoulos, 2014;Riby & Hancock, 2009;Rice, Moriuchi, Jones, & Klin, 2012;Q. Wang, Campbell, Macari, Chawarska, & Shic, 2018), biological motion (Falck-Ytter, Rehnberg, & Bölte, 2013;Klin, Lin, Gorrindo, Ramsay, & Jones, 2009), and following the gazes of others (Bedford et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ROIs typically include the face, eyes, mouth, body, objects, or other items of potential interest (e.g., an object that is being manipulated) (Chawarska et al, 2012;W Jones et al, 2008;Warren Jones & Klin, 2013). The second estimates the relative amount of time that children gaze at each side of a split screen that contains two different stimuli (e.g., children exercising on one side and geometrical shapes on the other (Moore et al, 2018;Pierce et al, 2016)). Both of these measures estimate gaze abnormalities using summary statistics that quantify the total amount of time that a child gazes at a particular stimulus, regardless of when they gazed at it (i.e., ignoring the temporal gaze pattern).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation